2017
DOI: 10.1016/j.chiabu.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with re-entry to out-of-home care among children in England

Abstract: Exiting and re-entering out-of-home care (OHC) is considered a disruption to permanence which may have long-lasting, negative consequences for children due to a lack of stability and continuity. Each year approximately one-third of children in OHC in England exit, but information is lacking on rates of re-entries and associated factors. Using national administrative data, we calculated rates of re-entry among children exiting OHC from 2007 to 2012, identified key child and care factors associated with re-entry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…We did not find difference in the time of separation, age at first out-of-home allocation, or sex. Some studies on the out-of-home care showed that reunification fails in almost 22-33% of the cases causing a re-entering of the child in the social care protection [13][14][15]. Others tried to outline likely risk factors due to the lack of reunification or the need to re-entry in the out-ofhome care after a failed reunion, showing opposing results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not find difference in the time of separation, age at first out-of-home allocation, or sex. Some studies on the out-of-home care showed that reunification fails in almost 22-33% of the cases causing a re-entering of the child in the social care protection [13][14][15]. Others tried to outline likely risk factors due to the lack of reunification or the need to re-entry in the out-ofhome care after a failed reunion, showing opposing results.…”
Section: Discussionmentioning
confidence: 99%
“…A generalization of these results is very difficult due to the unique and not always measurable factors, as the severity and length of the period of maltreatment experienced. Moreover, it is debated if the outplacement is really beneficial or inconsequential for the development and wellbeing of maltreated children [15,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Mortality registration records were linked to hospital records for the mother and infant. In England, de-identified data on inpatient admissions for all National Health Service (NHS) hospitals linked to Office for National Statistics mortality data were obtained from NHS Digital, linked between mother and infant using previously reported methods [30], and analyzed within the UCL Data Safe Haven, England [31]. In Ontario, hospital discharge records were obtained from the Canadian Institute for Health Information Discharge Abstract Database and the Ontario Mental Health Reporting System.…”
Section: Methodsmentioning
confidence: 99%
“…The UK survey/cohort data used in the published literature are: the National Child Development Study (NCDS), the Avon Longitudinal Study of Parents and Children, the Environmental Risk Longitudinal Twin Study (E‐Risk), and more recently the UK Biobank study. For what concerns the use of administrative data: two studies (Woodman et al., 2012; Chandan et al., 2019) have used primary care records, two studies (González‐Izquierdo et al., 2010, 2014) have used data from the Hospital Episode Statistics, two studies (Mc Grath‐Lone et al., 2016, 2017) have used administrative records on Children Looked After and two very recent studies (Murray et al., 2020a, 2020b) have used data from the Longitudinal Study; additionally, another recent study (Baldwin et al., 2020) has used the Born in Bradford cohort linked with data from the Child Protection System. This review also showed that using directly results from this literature as basis for our cost estimates was problematic, since different definitions of child maltreatment have been adopted (even in studies based on the same data, see Table of the Supplementary Material), and different methodologies and control variables have been used in the various studies.…”
Section: Literature Reviewmentioning
confidence: 99%